Physiological demands of men academy rugby union players at national level - Delforge, E.; Imbert, S.; Zamia, S.; Daussin, F. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: To make training effective, it is necessary to calibrate them according to the demands of the competition. While there is some data on senior elite and national level, there is little information about the physiological demands of a match in men academy rugby union players at national level. The aim of this study was to characterize the match activity of under 19 years old academy rugby union players in order to prescribe accurate trainings.